Bauran Pemasaran sebagai Upaya Peningkatan Daya Jual Jamu Seduh Tradisional - Sugiarto Sugiarto; Dyah Pitaloka; Anggraeni Hadi Pratiwi; Zainal Abidin; Arief Lukman; Dwi Nirnia Ari Cahyani (I-Com: Indonesian Community Journal, 2024)
ABSTRACT The lack of public interest in purchasing traditional brewed herbs is a result of the low supply of herbs required for consumption, although some argue that only sick people consume such medicines. This condition usually occurs in big cities. The aim of this activity is to increase the marketability of traditionally brewed herbs to the local community. The community service activity was carried out in Bumiaji, Batu, October 2023. The information collection method uses randomized respondents based on classification. Policy analysis using SWOT matrix approach. Selling techniques focus on market segments based on geographic, demographic, psychographic, and behavioral criteria. The target audience is young and elderly people who are interested in buying herbal medicine. Thanks to online sales promotion, the purchasing power of herbal medicine increased. The online marketing mix model increased the marketability of herbal medicine by 45%. Traditional medicine users appear to be 40% young and 60% elderly.